Short- and Long-Term Outcomes of Robotic Surgery for Rectal Neuroendocrine Tumor. (June 2022) - Saito, Kentaro; Yamaoka, Yusuke; Shiomi, Akio; Kagawa, Hiroyasu; Hino, Hitoshi; Manabe, Shoichi; Kato, Shunichiro; Hanaoka, Marie
Background . The optimal radical surgical approach for rectal neuroendocrine tumor (NET) is unknown. Methods . This study evaluated the short- and long-term outcomes of 27 patients who underwent robotic radical surgery for rectal NET between 2011 and 2019. Results . The median distance from the lower border of the tumor to the anal verge was 5.0 cm. The median tumor size was 9.5 mm. Six patients (22%) had lymph node metastasis. The incidences of postoperative complications of grade II and grade III or more according to the Clavien–Dindo classification were 11% and 0%, respectively. All patients underwent sphincter-preserving surgery, and no patients required conversion to open surgery. The median follow-up time was 48.9 months, and both the 3-year overall survival and relapse-free survival rates were 100%. Conclusions . Short- and long-term outcomes of robotic surgery for rectal NET tumor were favorable. Robotic surgery may be a useful surgical approach for rectal NET.